Male Accessory Gland Infection: Relevance of Serum Total Testosterone Levels - R. A. Condorelli; A. E. Calogero; E. Vicari; V. Favilla; S. Cimino; G. I. Russo; G. Morgia; S. La Vignera (International Journal of Endocrinology)
Aim of the present study was to evaluate the different ultrasound characterization of fertile symptomatic patients with MAGI (male accessory gland infection) according to different serum concentrations of total T (TT). We analyzed the ultrasound and hormonal data of 200 patients aged between 24.0 and 67.0 years. Patients were divided into six groups according to the sextile distribution of TT. Patients with serum concentrations of TT < 3.6 ng mL−1 had a higher mean duration of symptoms compared to the other examined groups. Patients with serum concentrations of TT > 6.6 ng mL−1 showed a frequency of ultrasound criteria suggestive for bilateral form of prostatitis and prostate-vesiculo-epididymitis and significantly lower compared to the other examined groups. At multivariate logistic regression analysis adjusted for age and BMI, TT was an independent predictive factor of prostatovesiculitis (OR = 0.818 [95% CI: 0.675–0.992]; P<0.01) and prostate-vesiculo-epididymitis (OR = 0.714 [95% CI: 0.578–0.880]; P<0.01), which represent the main forms of complicated MAGI. The results of this study suggest that male hypogonadism could be associated with a different ultrasound characterization of these patients.